2014
DOI: 10.1105/tpc.114.128611
|View full text |Cite
|
Sign up to set email alerts
|

CYCLIN-DEPENDENT KINASE8 Differentially Regulates Plant Immunity to Fungal Pathogens through Kinase-Dependent and -Independent Functions in Arabidopsis    

Abstract: CYCLIN-DEPENDENT KINASE8 (CDK8) is a widely studied component of eukaryotic Mediator complexes. However, the biological and molecular functions of plant CDK8 are not well understood. Here, we provide evidence for regulatory functions of Arabidopsis thaliana CDK8 in defense and demonstrate its functional and molecular interactions with other Mediator and non-Mediator subunits. The cdk8 mutant exhibits enhanced resistance to Botrytis cinerea but susceptibility to Alternaria brassicicola. The contributions of CDK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 79 publications
7
138
0
Order By: Relevance
“…1). Although med8, med13, and med18 have been shown to be more susceptible than the wild type to the necrotrophic fungal pathogens B. cinerea and A. brassicicola (Kidd et al, 2009;Lai et al, 2014;Zhu et al, 2014), they did not show enhanced susceptibility to S. sclerotiorum. This is probably because MED8, MED13, and MED18 do not play a major role in regulating S. sclerotiorum-induced transcriptome changes (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1). Although med8, med13, and med18 have been shown to be more susceptible than the wild type to the necrotrophic fungal pathogens B. cinerea and A. brassicicola (Kidd et al, 2009;Lai et al, 2014;Zhu et al, 2014), they did not show enhanced susceptibility to S. sclerotiorum. This is probably because MED8, MED13, and MED18 do not play a major role in regulating S. sclerotiorum-induced transcriptome changes (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…MED14, MED15, MED16, and MED19a have been shown to regulate the SA-triggered immunity against biotrophic and hemibiotrophic pathogens (Canet et al, 2012;Zhang et al, 2012Zhang et al, , 2013Caillaud et al, 2013), whereas MED8, MED12, MED13, MED16, MED21, MED25, and CDK8 have been found to function in JA/ET-mediated immunity against necrotrophic pathogens (Dhawan et al, 2009;Kidd et al, 2009;Zhang et al, 2012;Zhu et al, 2014). MED18 also functions in resistance to necrotrophic pathogens, but the resistance is independent of the JA/ET signaling (Lai et al, 2014).…”
mentioning
confidence: 99%
“…MED14, MED15 and MED16 contribute to SA-mediated plant local and systemic resistance to Pst (Zhang et al, 2013). CDK8, MED12 and MED13, the kinase module of the Mediator complex, also play important roles in plant immunity to necrotrophic fungi and Pst (Zhu et al, 2014). Systematic characterization of various PTI outputs triggered by purified MAMPs or Pst hrcC in individual Mediator complex mutants can help reveal whether and how Mediator directly conveys PRR signaling to selective activation of MAMP-responsive genes.…”
Section: Selective Activation Of the General Transcription Machinery mentioning
confidence: 99%
“…Notably, ERF1 and ORA59 regulate different JA-responsive genes from those regulated by MYC2 (Cevik et al, 2012). In addition, MED25 as well as its interacting subunit CDK8 also regulate the expression of ERF1 and ORA59 by binding to their promoters (Cevik et al, 2012; Zhu et al, 2014). Moreover, MED16 directly interacts with WRKY33, a member of the WRKY family of plant-specific transcription factors (discussed below in detail) and is essential for the recruitment of RNAPII to the WRKY33 target genes PDF1.2 and ORA59, suggesting a specific role of MED16 in mediating the transcriptional regulation of WRKY33 target genes (Wang et al, 2015).…”
Section: Selective Activation Of the General Transcription Machinery mentioning
confidence: 99%
“…The co-IP was conducted following the previously described procedure (Lai et al, 2014;Zhu et al, 2014). Briefly, the plasmids containing full-length HLS1-HA and MED18-MYC driven by the CaMV 35S promoter were generated and transformed into Agrobacterium.…”
Section: Co-ip Assaymentioning
confidence: 99%